Co-design com Prática Sustentável no Ensino de Design de Moda - Cuenca, Desamparados Pardo (Revista de Ensino em Artes, Moda e Design, 2020)
The issue of sustainability is presented today as one of the main challenges facing hypermodern society. Fashion designers and educators have the opportunity to adopt a fashion design paradigm, which departs from the classic structures of fast fashion and can guide them towards a new concept of ethical and sustainable fashion. From this approach it is possible to work with design, manufacturing and consumption criteria; but also reactivate the longevity of the garments, improving the user experience and the consideration of fashion waste. Our research is based on the concept of slow fashion and the application of co-design methods in classrooms, to encourage the development of sustainable practices and new collaborative methods in education, involving designers, researchers, craftsmen and different social groups and non-governmental organizations in the generation and development process. The qualitative methodological view was approached from the practice of participatory design in offline communities, where various design strategies for sustainability were implemented, such as; piracy, decoding and recoding techniques for second-hand clothing, all based on criteria of optimization and quality improvement of the garments. The sample included 30 participants divided into 5 groups, whose members adopted different roles and actions within the groups. Various data collection instruments were also used that measured awareness levels and sustainable positive impacts on workshop participants.